Medicago truncatula DNF2 is a PI‐PLC‐XD‐containing protein required for bacteroid persistence and prevention of nodule early senescence and defense‐like reactions. Issue 4 (27th December 2012) - Bourcy, Marie; Brocard, Lysiane; Pislariu, Catalina I.; Cosson, Viviane; Mergaert, Peter; Tadege, Millon; Mysore, Kirankumar S.; Udvardi, Michael K.; Gourion, Benjamin; Ratet, Pascal
Summary: Medicago truncatula and Sinorhizobium meliloti form a symbiotic association resulting in the formation of nitrogen‐fixing nodules. Nodule cells contain large numbers of bacteroids which are differentiated, nitrogen‐fixing forms of the symbiotic bacteria. In the nodules, symbiotic plant cells home and maintain hundreds of viable bacteria. In order to better understand the molecular mechanism sustaining the phenomenon, we searched for new plant genes required for effective symbiosis. We used a combination of forward and reverse genetics approaches to identify a gene required for nitrogen fixation, and we used cell and molecular biology to characterize the mutant phenotype and to gain an insight into gene function. The symbiotic gene DNF2 encodes a putative phosphatidylinositol phospholipase C‐like protein. Nodules formed by the mutant contain a zone of infected cells reduced to a few cell layers. In this zone, bacteria do not differentiate properly into bacteroids. Furthermore, mutant nodules senesce rapidly and exhibit defense‐like reactions. This atypical phenotype amongst Fix − mutants unravels dnf2 as a new actor of bacteroid persistence inside symbiotic plant cells.